Climate funds: time to clean up - Philippe Le Houérou (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
Over the last 30 years, at least 94 green-climate funds1 have been created to finance climaterelated projects and programs in Emerging Markets and Developing Countries (EMDC). Each individual fund may have been justified at the time of its creation. As a system, however, they do not add up and their contribution to the total flows of green finance remains marginal. In this paper, we counted 81 active funds as of end 2022. Moreover, it is quite difficult, if not impossible, to assess even the most basic aspects of the financial management and impact of these funds as a "system" and a channel of climate finance. Given the urgency to scale up both mitigation and adaptation policies and projects in EMDC, and before creating new funds that would add to the current astonishing fragmentation, it is urgent to drastically reduce the huge number of existing climate funds and to reform the remaining ones with a view to increasing their transparency, efficiency, synergies, and impact. That would be a useful first step into rationalizing and redefining the current messy aid architecture, even more so since most of these funds are publicly financed.
Keywords: 330